2012
DOI: 10.1029/2011jd016552
|View full text |Cite
|
Sign up to set email alerts
|

Wet removal of black carbon in Asian outflow: Aerosol Radiative Forcing in East Asia (A‐FORCE) aircraft campaign

Abstract: .[1] The Aerosol Radiative Forcing in East Asia (A-FORCE) aircraft campaign was conducted over East Asia in March-April 2009. During the A-FORCE campaign, 120 vertical profiles of black carbon (BC) and carbon monoxide (CO) were obtained in the planetary boundary layer (PBL) and the free troposphere. This study examines the wet removal of BC in Asian outflow using the A-FORCE data. The concentrations of BC and CO were greatly enhanced in air parcels sampled at 3-6 km in altitude over the Yellow Sea on 30 March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
211
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 123 publications
(222 citation statements)
references
References 74 publications
11
211
0
Order By: Relevance
“…As a result, the southern winds in the peninsula predominantly blew pollutants from the peninsula to the border provinces in China. The horizontal convergence of the mass flux of PM 2.5 in the boundary layer also caused upward transport to the free troposphere (Oshima et al, 2013) (Figs. 5(h)-5(k)).…”
Section: Monthly Impactmentioning
confidence: 99%
“…As a result, the southern winds in the peninsula predominantly blew pollutants from the peninsula to the border provinces in China. The horizontal convergence of the mass flux of PM 2.5 in the boundary layer also caused upward transport to the free troposphere (Oshima et al, 2013) (Figs. 5(h)-5(k)).…”
Section: Monthly Impactmentioning
confidence: 99%
“…Many studies have reported impacts of Asian aerosols on regional and hemispherical scales (e.g., Ramanathan et al, 2001;Carmichael et al, 2003;Adhikary et al, 2010;Matsui et al, 2011aMatsui et al, , b, 2013aOshima et al, 2012Oshima et al, , 2013. Several global and regional modeling studies have simulated and evaluated OA over East Asia (e.g., Heald et al, 2005Heald et al, , 2011Han et al, 2008;Matsui et al, 2009a;Utembe et al, 2011;Mahmud and Barsanti, 2013).…”
Section: H Matsui Et Al: Vbs Oa Simulation In East Asiamentioning
confidence: 99%
“…3.2). (Oshima et al, 2012). As described by Takami et al (2005Takami et al ( , 2007, the collection efficiency was assumed to be 0.5 at Fukue and 1.0 at Hedo.…”
Section: Simulation In and Aroundmentioning
confidence: 99%
“…Note that these initial parameters cover concentrations of chemical species from polluted urban air (e.g., BC = 10.0 µg m −3 and SO 2 = 10.0 parts per billion by volume (ppbv) at the surface in Beijing; Han et al, 2009;Takegawa et al, 2009) to free tropospheric air (e.g., BC = 0.1 µg m −3 and SO 2 = 0.1 ppbv in the free troposphere over the western Pacific; Russo et al, 2003;Oshima et al, 2012). The calculations were conducted using hourly photolysis rates for equinox at midlatitudes, although results obtained in this study can be applied irrespective of latitude and season (see Sects.…”
Section: Calculation Of Conversion Rate (1/τ Bc )mentioning
confidence: 99%